[Marcos pa rin ; Freedom Island ; New beginning [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
A debate on the return of the dead body of Ferdinand Marcos to the Philippines. Focuses situation of the residents in the Freedom Island also called Pulong Maria when they will be relocated. Takes a look at the career of Nora Aunor and the cancellation of her program in TV.
Marcos pa rin (16 min.) -- Freedom Island (13 min.) -- New beginning (15 min.)
VHS.
Keywords: Marcos, Ferdinand Edralin, 1917-1989 -- Death and burial; Aquino, Corazon Cojuangco, 1933- -- Political and social views; Aunor, Nora; Land use -- Philippines -- Manila; Squatters -- Philippines -- Paranaque; Philippines -- Politics and government, 1966-1986.; Pulong Maria (Paranaque) -- Economic conditions; Pulong Maria (Paranaque) -- Social conditions